Research progress on extraction, separation, structure, and biological activities of polysaccharides from jujube fruit (Ziziphus jujuba Mill.): a review - Jia, Feilong; Wang, Bo; Ma, Hui; Bai, Changcai; Zhang, Yuanyuan (Frontiers in Chemistry, 2025)
Jujube (Ziziphus Jujuba Mill.) is an excellent medicinal and edible plant owing to its high nutritional and health-promoting properties. As an important bioactive component, Z. Jujuba polysaccharides have aroused wide attention due to their various pharmacological activities, including anti-inflammatory, immunomodulatory, anti-oxidant, anti-tumor, anti-viral, regulating gut microbiota, hepatoprotective effects and prebiotic activity, and so on. This review highlights the advancements in the extraction methods, structural characteristics, structural elucidation, and functional analysis of polysaccharides derived from Jujube fruits over the past decade, aiming to provide valuable insights for future development and commercialization of Jujube fruits polysaccharides.